PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA DENGAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI (STUDI PADA PERANGKAT DESA SE KECAMATAN BATANG KABUPATEN BATANG) - Pramudito, Luksono; Yunianto, Askar (Jurnal Ilmiah Telaah Manajemen, 2009)
The purpose of this research examined and analyzed the Effect of Leadership, Motivation to Employee Performance with the Organizational Commitment as a mediation.The object of this research was employees atthe village of Batang Subdistrict. All member of population became sample research. The collecting data using the quistioner. The amount of responden 98. The Questioner completed only 96 respondent, 2 questioner failed (missing data). After the data was collected the data was examined validity and realiability. After that, the hypotesis exammined.The result, of this research represented that The Organizational Commitment as amediating variable could explain that the Effact of the Leadership, Motivation to Employee Performance.Key words:Leadership, Motivation, Employee Performance and Organization Commitment